Bridging Discrete and Backpropagation: Straight-Through and Beyond - Liu, Liyuan; Dong, Chengyu; Liu, Xiaodong; Yu, Bin; Gao, Jianfeng (NeurIPS 2023 (Oral), 2023)
Backpropagation, the cornerstone of deep learning, is limited to computing gradients solely for continuous variables. This limitation hinders various research on problems involving discrete latent variables. To address this issue, we propose a novel approach for approximating the gradient of parameters involved in generating discrete latent variables. First, we examine the widely used Straight-Through (ST) heuristic and demonstrate that it works as a first-order approximation of the gradient. Guided by our findings, we propose a novel method called ReinMax, which integrates Heun's Method, a second-order numerical method for solving ODEs, to approximate the gradient. Our method achieves second-order accuracy without requiring Hessian or other second-order derivatives. We conduct experiments on structured output prediction and unsupervised generative modeling tasks. Our results show that brings consistent improvements over the state of the art, including ST and Straight-Through Gumbel-Softmax.